PENINGKATAN PROSES PEMBELAJARAN TEMATIK MENGGUNAKAN MODEL BAMBOO DANCING DI SEKOLAH DASAR - YARSINA, FENILA (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
Abstract This research is motivated not maximal thematic teacher in the learning process. This condition can be seen from the teacher introduces the topic yet, has not created the group. The purpose of this study is to describe the use of the model Bamboo Dancing to improve belajar.Penelitian result of this is a class action (PTK) which uses qualitative and quantitative approaches. Conducted in two cycles, the first cycle consists of two meetings, and the second cycle consisted of one meeting. Research procedures including planning, implementation, observation, and reflection. The research subject is the teacher and second grade students of SDN 03 Feed Labuah town of Bukittinggi by the number of students 30 people. The results of the research cycle I to cycle II consecutively, RPP votes 66% (enough), and 82.14% (excellent). Activities teachers 71.9% (enough), and 93.75% (excellent). 71.9% student activity (enough), and 93.75% (excellent). Assessment of the learning process and results average class is 71 and 83. Keywords: Thematic; bamboo dancing